PENURUNAN KADAR ZAT WARNA RODAMIN B MENGGUNAKAN HUMIN HASIL ISOLASI DARI TANAH HUTAN DAMAR BATURRADEN - Tien Setyaningtyas; Roy Andreas (Universitas Jenderal Soedirman, 2007)
Humin was isolated from the Baturraden resin forest and purified use mixture of HCl:HF. Purified humin is characterised such as identify of functional group of humin, stipulating of water content, stipulating of dust content, obstetrical stipulating of total acidity content, carboxylic and OH phenolic functional group. The adsorption of rodamin by humin measured by UV-Visible spectrophotometer at maximum wavelength of rodamin B liquid, optimum pH and optimum contact time to determine absorbtion capacities and isotherm adsorption pattern .Humin that isolated from Baturraden resin forest have characteristic such as water content 16.6199 %; dust content 9.2050 %; total acidity content 475 cmol / Kg; carboxylic rate 200 cmol/Kg, and OH phenolic rate 275 cmol/Kg. Maximum wavelength of rodamin B is 554 nm and optimum contact time of adsorption rodamin B by humin is 180 minute with optimum pH 4. Adsorption rodamin B by humin follows the pattern of Langmuir isotherm adsorptionwith the value of R2 is 0.9801 and absorption capacities is 39,5257 mg/g.